Effect of lipoic acid and α‐glyceryl‐phosphoryl‐choline on astroglial cell proliferation and differentiation in primary culture. Issue 1 (26th October 2013) - Grasso, S.; Bramanti, V.; Tomassoni, D.; Bronzi, D.; Malfa, G.; Traini, E.; Napoli, M.; Renis, M.; Amenta, F.; Avola, R.
<x xml:space="preserve">Abstract</x> Lipoic acid plays a crucial role as antioxidant and metabolic component of enzymes involved in glucose metabolism of different cell types. Choline alphoscerate (α‐glyceryl‐phosphoryl‐choline [αGPC]) is a semisynthetic derivative of phosphatidylcholines representing, among acetilcholine precursors, a cholinergic drug. In the present study, we evaluated the expression of some proliferation and differentiation markers in 15 or 21 DIV astrocyte cultures treated with 50 μM (+)lipoic acid or (+/−)lipoic acid and/or 10 mM αGPC for 24 hr. In addition, we evaluated the possible genoprotective effect by analysis of DNA status detected by alkaline comet assay. The addition of single drugs [(+)lipoic acid, (+/−)lipoic acid, or αGPC] induced an "upward modulation" of the expression of biomarkers used in our study. On the contrary, the cotreatment with either (+)lipoic acid + αGPC or (+/−)lipoic + αGPC surprisingly showed no significant modification or even a downregulation of the above‐mentioned biomarkers. This latter finding demonstrated no additional effect after the cotreatment with both drugs with respect to the single treatments alone. Further studies are necessary to clarify the specific mechanism evoked by the processing of these neuroprotective agents in our in vitro models. Finally, these preliminary findings may represent a good tool with which to clarify the antioxidant and metabolic roles played by lipoic acid in proliferating and differentiating astroglial cell cultures, during an interactive cross‐talk between glial and neuronal cells, after brain lesions or damage correlated with oxidative stress that may occur in some degenerative diseases. © 2013 Wiley Periodicals, Inc.